Twitter and Social Services : Analysis of Political and Citizen Discourse in Spain 2015-2019 - Chaves-Montero, Alfonso (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Social networks play an important role in society. This research focuses on analysing the messages issued on Twitter on the topics of social services in Spain, both in the political discourse and that of citizens during the different electoral campaigns that have taken place in Spain from 2015 to 2019. The sample consists of 6.728 tweets on the topic “social services”. A quantitative analysis was carried out using the Gephi application. The conclusion is that politicians do not respond to citizens’ demands in terms of social policies and social services on Twitter.